Skin cancers arising within tattoos: A systematic reviewCapsule Summary - Jamie Lebhar, BME; Jennifer Jacobs, BS; Chandler Rundle, MD; Samantha J. Kaplan, PhD, MLIS; Paul J. Mosca, MD, PhD, MBA (Elsevier, 2024)
Background: Tattooing is a widespread practice and has increased in popularity over time. Many lesions have been described in relation to tattoos, including malignant tumors. Objectives: The primary goal of this review is to determine whether the frequency of published cases of skin cancers within tattoos has been increasing over time. Methods: Our review is in adherence to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and reporting criteria. The databases MEDLINE via PubMed, Embase via Elsevier, and Scopus via Elsevier were searched from inception to February 23, 2023. No data or publication date limits were imposed. Results: Our review identified 160 cases of cutaneous tumors arising within tattoos. An increase in published cases over time was observed. Most reported tumors developed within red tattoo pigment (36.9%), with the largest contribution by squamous cell carcinoma and keratoacanthoma lesions. Limitations: There was a lack of consistency of information in published case reports which limited the scope of our analysis. Small sample size was also a limitation of this review. Conclusions: With the increased popularity of tattoos, it is helpful to continue reporting cases of cutaneous malignancies within tattoos. Awareness of the frequency and severity of tumors within tattoos may be communicated to the public.